2011
DOI: 10.1159/000324392
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effects of Smoking and Hypercholesterolemia on the Risk of Stroke and Coronary Heart Disease in Japanese: The Hisayama Study

Abstract: Background: Cigarette smoking is an established risk factor for stroke and coronary heart disease (CHD) in Western countries. However, it is uncertain whether or not smoking raises the risk of stroke in Japanese. We examined the influence of smoking on the development of stroke and CHD and the effects of interactions between smoking and hypercholesterolemia on these outcomes in a general Japanese population. Methods: A total of 2,421 community-dwelling Japanese individuals, aged 40–79 years, with no history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 48 publications
2
24
1
Order By: Relevance
“…This result is primarily supported by a previous study in a cohort of 2,421individuals who have similar characteristics with the present subjects followed up for 14 years. 30 According to Table 1, however, past smokers have normal MetS parameters including BMI, waist circumference, BP, UA, TG, LDL-C and HDL-C and HbA1c, which are equal to those of never smokers. This is possibly in part due to the relatively small size of the data set, because the data in Table 2 differ from those in previous reports that suggested waist circumference 31 or HDL-C 32 as independent risk factors for accelerated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…This result is primarily supported by a previous study in a cohort of 2,421individuals who have similar characteristics with the present subjects followed up for 14 years. 30 According to Table 1, however, past smokers have normal MetS parameters including BMI, waist circumference, BP, UA, TG, LDL-C and HDL-C and HbA1c, which are equal to those of never smokers. This is possibly in part due to the relatively small size of the data set, because the data in Table 2 differ from those in previous reports that suggested waist circumference 31 or HDL-C 32 as independent risk factors for accelerated atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking was not associated with intracerebral hemorrhage. Similarly, the Hisayama Study 44 in Japan reported that smoking was a significant risk factor for ischemic stroke, subarachnoid hemorrhage, and CAD, but not for intracerebral hemorrhage. The Japan Public Health Center-based Prospective Study on Cancer and Cardiovascular Disease (JPHC) Study 45 also reported that smoking raised the risks of ischemic stroke and subarachnoid hemorrhage.…”
Section: Smokingmentioning
confidence: 92%
“…17 Another prospective cohort study of 2421 Japanese also did not find any association of smoking with hemorrhagic stroke. 18 As the number of deaths from hemorrhagic stroke in Japan has decreased sharply since about 1965, less than one quarter of the stroke deaths were classified as cerebral hemorrhage. 19,20 Small studies might not have sufficient events for reliable prospective analysis, especially in populations with a low incidence and mortality of hemorrhagic stroke.…”
Section: August 2013mentioning
confidence: 99%